KAMUS BAHASA DAERAH TORAJA – INDONESIA BERBASIS WEB - Eko Pasinggi; Gidion Aryo Nugraha Pongdatu (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2024)
Indonesia is a country rich in linguistic diversity, with thousands of regional languages spread across the archipelago. However, this diversity also brings serious problems, as many of these languages face the risk of extinction or even near extinction. To maintain the survival of a language, the availability of a reference in the form of a dictionary is of key importance. One of the local languages facing such challenges is Toraja. Toraja is one of the local languages in Indonesia that has a rich history and culture. Although there is already a Toraja language dictionary available, the number is limited, which makes it difficult for some people to utilize it. However, with the development of information and communication technology, there is new hope to overcome this challenge. This research aims to develop a prototype of a web-based Toraja language dictionary. The system is designed to provide easier and wider access to the Toraja language dictionary, thus helping to preserve and enrich the language. The test results show that the system has features that function properly and are able to provide accurate translation results. With this web-based Toraja language dictionary prototype, it is hoped that Toraja people and language researchers can easily access information on their language and promote the sustainability of Toraja language.